2016
DOI: 10.1007/s10796-016-9679-1
|View full text |Cite
|
Sign up to set email alerts
|

Open data and its usability: an empirical view from the Citizen’s perspective

Abstract: Government legislation and calls for greater levels of oversight and transparency are leading public bodies to publish their raw datasets online. Policy makers and elected officials anticipate that the accessibility of open data through online Government portals for citizens will enable public engagement in policy making through increased levels of fact based content elicited from open data. The usability and benefits of such open data are being argued as contributing positively towards public sector reforms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 66 publications
(82 reference statements)
4
125
0
3
Order By: Relevance
“…We found that the technology attributes (i.e., performance expectancy and effort expectancy) had direct effects on attitude and behavioural intention Weerakkody et al 2017). This implies that the individuals attribute considerable importance to the extent to which the technology in question may be useful and easy to use.…”
Section: Implications For Practicementioning
confidence: 80%
“…We found that the technology attributes (i.e., performance expectancy and effort expectancy) had direct effects on attitude and behavioural intention Weerakkody et al 2017). This implies that the individuals attribute considerable importance to the extent to which the technology in question may be useful and easy to use.…”
Section: Implications For Practicementioning
confidence: 80%
“…The citizens are one of the most important stakeholders of such developments. Hence, in order to avoid resistance from stakeholders and failure of such initiatives Hughes et al 2016Hughes et al , 2017, the perceptions of citizens and government employees towards various aspects of smart cities should also be explored by utilising established theories and models (see for example, AlAlwan et al 2017;Dwivedi et al 2011aDwivedi et al , 2011bDwivedi et al , 2013Dwivedi et al , 2016Dwivedi et al , 2017bDwivedi et al , 2017cHossain and Dwivedi 2014;Kapoor et al 2014aKapoor et al , 2014bKapoor et al , 2015Rana and Dwivedi 2015;Rana et al 2015aRana et al , 2015bRana et al , 2016Rana et al , 2017Shareef et al 2011Shareef et al , 2016aShareef et al , 2016bShareef et al , 2017Sinha et al 2017;Slade et al 2015;Veeramootoo et al 2018;Weerakkody et al 2013Weerakkody et al , 2017) from information systems and electronic government domains.…”
Section: Limitations and Future Scopementioning
confidence: 99%
“…The paper BOpen Data and its Usability: An Empirical View from the Citizen's Perspective^by Weerakkody et al (2017) investigate predictors for the acceptance and use of public sector open data. For this, Rogers' diffusion of innovations theory (DOI) is enhanced.…”
Section: Papers Overviewmentioning
confidence: 99%